2022
DOI: 10.1111/pce.14328
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the primary salicylic acid hydroxylases in rice enhances broad‐spectrum resistance against pathogens

Abstract: Salicylic acid (SA) is a crucial hormone involved in plant immunity. Rice (Oryza sativa) maintains high SA levels that are not induced by pathogens. However, the roles of SA in rice immunity and yield remain largely unknown. Here, we identified SA 5-hydroxylases 1 (OsS5H1) and 2 (OsS5H2) as the primary enzymes engaged in catalysing SA to 2,5-dihydroxybenzoic acid (2,5-DHBA) in rice. SA levels were significantly increased in the oss5h mutants, while they were dramatically decreased in the OsS5H1 and OsS5H2 over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 42 publications
3
29
1
Order By: Relevance
“…This implies that these genes may be candidate targets for engineering crops with enhanced resistance to pathogens ( Figure 2 a). Until now, the CRISPR/Cas9-mediated mutation of a DMR6 ortholog has conferred BSR in tomato and rice [ 59 , 64 , 65 , 66 ]. Intriguingly, the disruption of the DMR6 ortholog does not influence the yield per plant of tomato and rice [ 59 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that these genes may be candidate targets for engineering crops with enhanced resistance to pathogens ( Figure 2 a). Until now, the CRISPR/Cas9-mediated mutation of a DMR6 ortholog has conferred BSR in tomato and rice [ 59 , 64 , 65 , 66 ]. Intriguingly, the disruption of the DMR6 ortholog does not influence the yield per plant of tomato and rice [ 59 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the CRISPR/Cas9-mediated mutation of a DMR6 ortholog has conferred BSR in tomato and rice [ 59 , 64 , 65 , 66 ]. Intriguingly, the disruption of the DMR6 ortholog does not influence the yield per plant of tomato and rice [ 59 , 65 ]. Moreover, elevated resistance to a single pathogen has been reported in banana, sweet basil, and potato via the inactivation of a DMR6 ortholog by the CRISPR/Cas9 system [ 58 , 60 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SA is an indispensable hormone involved in plant immunity, and SA homeostasis in plants determines the broad-spectrum and durable resistance to pathogens and diseases. , In our study, we explored the effects of exogenous SA on the secondary metabolic pathways in tea plants. It was found that SA treatment inhibited the expression of genes in the phenylpropanoid and flavonoid pathway but promoted the lignin metabolic pathway (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…OsS5H/FNS-03g was reported by independent studies to have either S5H or FNS activities (Kim et al, 2008;Liu et al, 2023;Zhang et al, 2022). Therefore, we investigated whether the protein possesses both S5H and FNS activities.…”
Section: Oss5h/fns-03g Is a Bifunctional Protein With S5h And Fns Act...mentioning
confidence: 98%